The Use of Single Length Technique for Single Visit Root Canal Treatment on Molar Mandibula: A case report - Nugroho, Juni J.; T., Andi F. (Hasanuddin University, 2021)
Objective: This case report describe the one visit root canal treatment on molar mandibula using a single length technique.Methods: A 28 year old male came to RSGMP with complaints of caries and pain on lower back teeth, positive on cold thermal stimuli, negative on percussion and palpation. Radiographs show caries has reached the pulp chamber.Result: Root canal were treated with single visit endodontic treatment used single length technique, with composite direct restoration. There were no subjective and objective complaints after 1 week control.Conclusion: The use of single length technique on single visit endodontic treatment gives good and efficient result.